Rockfall research: a bibliometric analysis and future trends - Briones Bitar, Josué (2020)
Rockfall is one of the main phenomena in mountainous environments due to its fast and high speed of movement, its unpredictability, and, therefore, the di culty of identifying signs of instability and detachment of the blocks. Compared to other types of sliding, the proportion of rockfall research is smaller and sometimes little known, but, in the last five years, rapid growth in this area has been shown. Therefore, this research aimed to review the intellectual structure of rockfall, through analysis of scientific production using bibliometric techniques that allow its analysis, knowledge, global evolution, and future trends in rockfall. The research methodology consists of three steps: (1) data compilation, (2) software and data cleaning, and (3) analysis, interpretation, and visualization. This analysis focuses on the period from 1975 to 2019. For the data, a total of 811 academic publications were retrieved from the Scopus database. The results indicate an increasing trend of annual publications on rockfall. This analysis reveals the main topics, countries, and most influential institutions in the world that have carried out relevant research in scientific publications; it also shows the journals that have the most publications. VOSviewer software was adopted to evaluate the co-occurrence of author keywords. Currently, the hotspots rockfall issues mainly include: hazard-risk assessment, remote sensing, and rockfall monitoring. Finally, this article analyzes the limitations of current research and proposes a future direction for the development of new research.